The Role Of Gyugun Officers In Maintaining Indonesian Independence In Palembang During The Physical Revolution (1945-1949) - Pedo Nopansyah; Alian Alian; Farida Farida (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2018)
The tittle of the research was the role of officer Gyugun in defending the independence of Indonesia in Palembang in the physical revolution (1945-1949) with the arrangment issues : how the role of officer Gyugun in to defending the proclamation in Palembang. As for the purpose of this research was to know how history and role of officer Gyugun military in Palembang. This research had done since September until Desember 2017 in Palembang and around it using a method historically by collection of data from transcript and books or the study literature. The research result showed that when Japan dominated Palembang, from a military organization Gyugun after the end of the occupation of Japan, officer Gyugun took the lead in protecting our country’sovereignty from the allies and the Netherlands in Palembang. The officer Gyugun had a big important role in the history of the established of the army and became a lead of the struggle of the soldiers in the physical revolution in Palembang.